RAS-pathway mutation patterns define epigenetic subclasses in juvenile myelomonocytic leukemia - Lipka, Daniel B; Witte, Tania; Toth, Reka; Yang, Jing; Wiesenfarth, Manuel; Nöllke, Peter; Fischer, Alexandra; Brocks, David; Gu, Zuguang; Park, Jeongbin; Strahm, Brigitte; Wlodarski, Marcin; et al. (Nature communications, 2017)
Juvenile myelomonocytic leukemia (JMML) is an aggressive myeloproliferative disorder of early childhood characterized by mutations activating RAS signaling. Established clinical and genetic markers fail to fully recapitulate the clinical and biological heterogeneity of this disease. Here we report DNA methylome analysis and mutation profiling of 167 JMML samples. We identify three JMML subgroups with unique molecular and clinical characteristics. The high methylation group (HM) is characterized by somatic PTPN11 mutations and poor clinical outcome. The low methylation group is enriched for somatic NRAS and CBL mutations, as well as for Noonan patients, and has a good prognosis. The intermediate methylation group (IM) shows enrichment for monosomy 7 and somatic KRAS mutations. Hypermethylation is associated with repressed chromatin, genes regulated by RAS signaling, frequent co-occurrence of RAS pathway mutations and upregulation of DNMT1 and DNMT3B, suggesting a link between activation of the DNA methylation machinery and mutational patterns in JMML.
Keywords: mutace; juvenilní myelomonocytární leukemie; Proto-Oncogene Proteins p21(ras); epigenomika; Epigenomics; Female; Infant; dítě; předškolní dítě; Protein Tyrosine Phosphatase, Non-Receptor Type 11; ženské pohlaví; mutační analýza DNA; biopsie; Leukemia, Myelomonocytic, Juvenile; Chromatin; Up-Regulation; protoonkogenní proteiny c-cbl; Proto-Oncogene Proteins c-cbl; DNA-(cytosin-5)-methyltransferasa 1; lidé; DNA-methyltransferasa 3B; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; Antineoplastic Agents; protinádorové látky; upregulace; DNA Mutational Analysis; signální transdukce; Mutation; Noonan Syndrome; metylace DNA; Signal Transduction; prognóza; regulace genové exprese u leukemie; DNA Methyltransferase 3B; DNA-(cytosin-5-)methyltransferasa; Noonanové syndrom; prospektivní studie; Male; kojenec; DNA (Cytosine-5-)-Methyltransferases; Biopsy; Prospective Studies; DNA (Cytosine-5-)-Methyltransferase 1; Child, Preschool; chromatin; DNA Methylation; Prognosis; Gene Expression Regulation, Leukemic; tyrosinfosfatasa nereceptorového typu 11; Child; mužské pohlaví; protoonkogenní proteiny p21(ras); Humans